Strong piezoelectricity in 3R-MoS₂ flakes - Hallil, Hamida (2022)
Distinct from conventional 2H-MoS2, recently synthesized 3R-MoS2 exhibits a noncentrosymmetric atomic structure of the trigonal “building blocks” and, thus, remarkable piezoelectric characteristics of ultrathin 3R-MoS2 flakes are predicated theoretically. This paper reveals, for the first time, very high piezoelectricity in 3R-MoS2 flakes experimentally. Through applying mechanical stress to a 48 nm 3R-MoS2 flake, a high output power density of 65 mW m-2 is obtained and is at least one order larger than those from the corresponding monolayer MoS2 flake. With out-of-plane lateral piezoresponse force microscopy technique, the two piezoelectric coefficients d33 and d13 are analyzed to be ≈0.9 and ≈1.6 pm V-1, respectively. These piezoelectric coefficients are not apparently dependent on the flake thickness. The findings suggest that 3R-MoS2 is of excellent piezoelectric properties and it can be an excellent material for novel piezoelectric devices.